Caracterização tecnológica do monzogranito serra Branca (Ceará, Brasil) - Marques, J.; Azevedo, M. R.; Neto, J. A. Nogueira; Pereira, A. J.S.C.; Artur, A. C. [UNESP] (My University, 2014)
The main objective of this investigation was to assess the viability of the commercial exploitation of the Serra Branca monzogranite as dimension stone. The Serra Branca massif belongs to a large late tectonic plutonic complex of Brasilian age (≈ 600 Ma), known in the literature as Quixeramobim batholith, that crops out in the Ceará Central Domain (NE Brazil). The work involved detailed geological mapping of a small sector of the batholith, petrography of the main lithologies and, at a subsequent stage, selection of a subset of samples from the Serra Branca monzogranite for technological and radiological characterization. The technological properties of the analysed samples satisfy the requirements proposed by ABNT NBR 15844 (2010) and ASTM C- 615 (2005) for use as building materials. On the other hand, the gamma index values (I) and radon exhalation rates are also low, certifying the quality of Serra Branca monzogranite as potential natural stone resources.
Technological characterization of the serra branca monzogranite (Ceará, Brasil)
Keywords: Ceará Central domain; Decorative dimension stones; Serra Branca facies